Quality of Life in SMA Patients Under Treatment With Nusinersen - Mix, Lucas; Winter, Benedikt; Wurster, Claudia D.; Platen, Sophia; Witzel, Simon; Uzelac, Zeljko; Graf, Heiko; Ludolph, Albert C.; Lulé, Dorothée (Frontiers in Neurology, 2021)
Background: Spinal Muscular Atrophy (SMA) is a severe neurodegenerative disease with no effective treatment until the recent development of the antisense oligonucleotide nusinersen. It is the first available drug with the potential to slow down or stop disease progression with a potentially major impact on patients’ wellbeing. Objective: This study set out to evaluate quality of life (QoL) in paediatric and adult patients over the course of therapy. Methods: 26 SMA patients receiving nusinersen were evaluated for global QoL (gQoL), health-related QoL (HRQoL) and depressiveness. Assessments were carried out three times over the first six months of treatment. Applied were different questionnaires: the Anamnestic Comparative Self-Assessment (ACSA) for gQoL, the Short Form-36 Health Survey (SF-36) for HRQoL in adult patients and the ALS Depression Inventory 12 Items (ADI-12) for depressiveness. The sample was matched with 22 healthy controls. Results: Despite severe physical restrictions, patients reported high levels of QoL and low levels of depressiveness at study entry, compared to controls. Early disease onset and low levels of physical functioning were predictors for better gQoL and lower levels of depressiveness. A significant decrease of gQoL in patients was evident over the course of the study. Still, adult patients reported a significant increase in perceived health. Conclusions: Our study provides first insight that SMA patients experience a gQoL superior to healthy controls at start of therapy. This might indicate patients’ high hopes and expectations towards treatment. gQoL returns to a level similar to that of healthy controls over the course of therapy.